Role of hedgehog signaling in the pathogenesis and therapy of heterotopic ossification - Pei, Yiran; Liu, Fangzhou; Zhao, Yike; Lin, Hui; Huang, Xiaoyan (Frontiers in Cell and Developmental Biology, 2024)
Heterotopic ossification (HO) is a pathological process that generates ectopic bone in soft tissues. Hedgehog signaling (Hh signaling) is a signaling pathway that plays an important role in embryonic development and involves three ligands: sonic hedgehog (Shh), Indian hedgehog (Ihh) and desert hedgehog (Dhh). Hh signaling also has an important role in skeletal development. This paper discusses the effects of Hh signaling on the process of HO formation and describes several signaling molecules that are involved in Hh-mediated processes: parathyroid Hormone-Related Protein (PTHrP) and Fkbp10 mediate the expression of Hh during chondrogenesic differentiation. Extracellular signal-regulated kinase (ERK), GNAs and Yes-Associated Protein (YAP) interact with Hh signaling to play a role in osteogenic differentiation. Runt-Related Transcription Factor 2 (Runx2), Mohawk gene (Mkx) and bone morphogenetic protein (BMP) mediate Hh signaling during both chondrogenic and osteogenic differentiation. This paper also discusses possible therapeutic options for HO, lists several Hh inhibitors and explores whether they could serve as emerging targets for the treatment of HO.